Analisis Faktor-faktor Penyebab Rendahnya Minat Baca Siswa Kelas V SD Negeri 184 Pekanbaru - Aini, Orin Tul; Kurniaman, Otang; Antosa, Zariul (Darul Yasin Al Sys, 2024)
This research aims to describe the factors that cause the low interest in reading in class V students at SD Negeri 184 Pekanbaru. The subjects of this research were 114 class V students, with 5 students from class VA, 5 students from class VB, and 4 people from class VC. Apart from fifth grade students who were used as research subjects. The method in this research uses a qualitative descriptive approach. Data collection techniques in this research use including interviews, observation, documentation. The data processing and analysis process is carried out by collecting data by reduction, the reduced data is then presented in a data presentation, then after that the data is verified to draw conclusions. The conclusions in this research were made with the aim of answering the problem formulation in this research, namely